Assistants' in nursing perceptions of their social place within mental health‐care settings. (29th May 2015) - Cowan, Darrin; Frame, Nicholas; Brunero, Scott; Lamont, Scott; Joyce, Mark
Abstract An international nurse shortage, tightening fiscal constraints, and increased service demands have seen health systems increasingly turn to employing assistants in nursing (AIN) as a cost‐effective means to meet demand. This paper describes social positioning from the perspective of 11 AIN who were employed to work in specialist mental health settings in a metropolitan health service in Sydney. Data was collected by means of semistructured interviews. Interview questions encouraged AIN to explore their experience with reference to positioning within the service, role perception, role development, staff relationship, and role satisfaction. Thematic analysis was utilized to generate themes and explore meaning within the data. The following themes emerged: role definition and clarity; socialization and adaptation; and enhancing education. Analysis suggests that whilst AIN were integrated into mainstream service, the scope of activities or role remains geographically variable and inconsistent. Encouragingly, as AIN became familiar with their work environments and teams, they considered themselves to be of value and were able to play a meaningful role. A desire for learning and a need for continuing education also emerged as a primary theme. Findings from the data suggest that AIN in the mental health setting remain a novel and, to some extent, poorly utilized resource.